Cohabitation and family formation in Japan - James M. Raymo; Miho Iwasawa; Larry Bumpass (Osaka University, Institute of Social and Economic Research (ISER), 2008)
This paper documents the prevalence, duration, and marital outcomes of cohabiting unions in Japan. It then examines the correlates of cohabitation experiences and describes differences in the family formation trajectories of women who have and have not cohabited. Cohabitation has increased rapidly among recent cohorts of women and cohabiting unions in Japan tend to be relatively short and almost as likely to dissolve as to result in marriage. Life table analyses demonstrate that the cumulative probabilities of marriage and parenthood are roughly similar for women who did and did not cohabit. The most notable difference is in the pathways to family formation, with women who cohabited more likely to both marry subsequent to pregnancy and delay childbearing within marriage. Taken as a whole, these results suggest that cohabiting unions in Japan are best viewed as an emerging stage in the marriage process rather than as an alternative to marriage or singlehood. We conclude with speculation about the likelihood of further increases in cohabitation in Japan and the potential implications for marriage and fertility.
Keywords: 330